Cerebellar Subjects Show Impaired Adaptation of Anticipatory EMG During Catching - Lang, Catherine E; Bastian, Amy J (Journal of neurophysiology, 1999)
1 Program in Physical Therapy and 2 Department of Anatomy and Neurobiology, Washington University School of Medicine, St. Louis, Missouri 63108 Lang, Catherine E. and Amy J. Bastian. Cerebellar Subjects Show Impaired Adaptation of Anticipatory EMG During Catching. J. Neurophysiol. 82: 2108-2119, 1999. We evaluated the role of the cerebellum in adapting anticipatory muscle activity during a multijointed catching task. Individuals with and without cerebellar damage caught a series of balls of different weights dropped from above. In Experiment 1 (light-heavy-light), each subject was required to catch light balls ( baseline phase ), heavy balls ( adaptation phase ), and then light balls again ( postadaptation phase ). Subjects were not told when the balls would be switched, and they were required to keep their hand within a vertical spatial "window" during the catch. During the series of trials, we measured three-dimensional (3-D) position and electromyogram (EMG) from the catching arm. We modeled the adaptation process using an exponential decay function; this model allowed us to dissociate adaptation from performance variability. Results from the position data show that cerebellar subjects did not adapt or adapted very slowly to the changed ball weight when compared with the control subjects. The cerebellar group required an average of 30.9 ± 8.7 trials (mean ± SE) to progress approximately two-thirds of the way through the adaptation compared with 1.7 ± 0.2 trials for the control group. Only control subjects showed a negative aftereffect indicating storage of the adaptation. No difference in performance variability existed between the two groups. EMG data show that control subjects increased their anticipatory muscle activity in the flexor muscles of the arm to control the momentum of the ball at impact. Cerebellar subjects were unable to differentially increase the anticipatory muscle activity across three joints to perform the task successfully. In Experiment 2 (heavy-light-heavy), we tested to see whether the rate of adaptation changed when adapting to a light ball versus a heavy ball. Subjects caught the heavy balls (baseline phase), the light balls (adaptation phase), and then heavy balls again (postadaptation phase). Comparison of rates of adaptation between Experiment 1 and Experiment 2 showed that the rate of adaptation was unchanged whether adapting to a light ball or a heavy ball. Given these findings, we conclude that the cerebellum is important in generating the appropriate anticipatory muscle activity across multiple muscles and modifying it in response to changing demands though trial-and-error practice.